Operational Excellence A Concise Guide to Basic Concepts and Their Application - Issar, Gilad; Navon, Liat Ramati (Management for Professionals, 2016)
As industrial companies are placing a higher focus on operations, this book comes at the right time with a compilation of basic concepts of Operational Excellence and their application. Operational excellence allows companies to recover from reductions in gross margins and low profitability, which largely occur due to a rise in agile competition and the short life span of new technologies. This book helps managers and consulting academicians as a ready reference for cross-industry implementation of operational excellence.